Changes in Nutrient Declaration After the Food Labeling and Advertising Law in Chile: A Longitudinal Approach - Pizarro-Quevedo, T (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Chile has implemented several strategies to decrease the burden of obesity and chronic diseases. The Food Labeling and Advertising Law (Law 20.606) requires a front-of-package “high in” warning label when energy and nutrients of concern (ENC) (total sugar, saturated fats, sodium) exceed established limits. This study aims to evaluate the impact of Law 20.606 on the ENC declaration of packaged foods in Chile, before and after the law implementation. We analyzed food nutritional labeling declarations from 70% of the most consumed packaged foods in Chile. Data collection was conducted in 2013 and 2019 in Santiago. Pictures from all sides of the package were taken from 476 products, classified into 16 food groups. All food groups had changes in the ENC declaration during the study period. Total sugar content showed the highest reduction (−15.0%; p = 0.001). Dairy, confitures and similar and sugary beverages had the greatest reduction in energy and total sugar content (p < 0.01). Energy, total sugar and sodium front of package “high in” simulation was significantly reduced in dairy, sugary beverages, flour-based foods, confitures and similar, fish and seafoods, fats and oils, spices, condiments and sauces and sugars (p < 0.05). We observed that companies reformulated products to adapt to the new regulation. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.